A structured histopathology‐based analysis of surgical outcomes in chronic rhinosinusitis with and without nasal polyps. Issue 5 (21st August 2019) - Marino, Michael J.; Garcia, J. Omar; Zarka, Matthew; Lal, Devyani
Abstract : Objectives: Structured histopathology reporting has been recently described for detailing immunopathological characteristics of chronic rhinosinusitis (CRS), and can be utilized for subtyping CRS and personalizing management. This study scrutinized elements of structured histopathology to identify characteristics that prognosticate outcomes following endoscopic sinus surgery (ESS) for CRS patients with nasal polyps (CRSwNP) and without nasal polyps (CRSsNP). Methods: Outcomes following ESS were measured using the patient‐reported 22‐item sinonasal outcome test (SNOT‐22). Changes in total SNOT‐22 scores at 6 and 12 months postoperatively were analyzed. Thirteen parameters reported in structured histopathology of sinus surgical tissue were studied for association with outcomes postsurgery. The overall cohort of all CRS patients was studied, along with subgroup analyses of CRSwNP and CRSsNP patients. Results: In the entire CRS cohort (n = 171), eosinophil count >10 per high power field (HPF) was associated with greater improvement in SNOT‐22 scores at 6 months post‐ESS ( P = .039). At 12 months follow‐up, no histopathological characteristic was associated with change in total SNOT‐22 score. In the CRSwNP (n = 66) subgroup, the presence of fibrosis ( P = .006) and eosinophil count ≤10 per HPF ( P = .025) were associated with less favorable changes in SNOT‐22 scores at 12 months follow‐up. Fibrosis remained statistically significant in multivariable analysis ( P = .007). Conclusions: At 6 months post‐ESS, tissue eosinophilia is associated with significantly higher improvement in SNOT‐22 scores, but this difference is diluted by 12 months. Fibrosis was associated with less favorable outcomes in SNOT‐22 scores for CRSwNP patients at 12 months and may be a prognosticator for poorer long‐term outcomes. Level of Evidence: 4